Whispering-Gallery-Mode Resonator-Based Hybrid Cavity for Mode Stabilization of a Fiber Laser - Cong Guang Wen; Bingliang Liu; Jia qiu; Huiying Xu; Beier Hu; Kaijun Che; Zhiping Cai (IEEE Photonics Journal, 2021)
The performances of a fiber laser stabilized by a whispering-gallery-mode(WGM) resonator depends heavily on the coupling of the resonator and fiber system, and is labile due to the lasing mode competitions among excitable WGMs. Here, we propose a hybrid cavity where a linear fiber cavity is coupled by a WGM resonator for dual stabilizations of the laser mode, and experimentally demonstrate single-mode lasing emission with stable and high signal to noise ratio (up to 61 dB), narrow linewidth (low to ∼5 kHz) operations. By adjusting the coupling of the linear fiber cavity and the WGM resonator, the fiber laser can operate in two- to four- mode lasing without mode hopping as well.